Detection of splice isoforms and rare intermediates using multiplexed primer extension sequencing. (January 2019) - Xu, Hansen; Fair, Benjamin; Dwyer, Zachary; Gildea, Michael; Pleiss, Jeffrey
Abstract Targeted RNA sequencing (RNA-seq) aims to focus coverage on areas of interest that are inadequately sampled in standard RNA-seq experiments. Here we present multiplexed primer extension sequencing (MPE-seq), an approach for targeted RNA-seq that uses complex pools of reverse-transcription primers to enable sequencing enrichment at user-selected locations across the genome. We targeted hundreds to thousands of pre-mRNA splice junctions and obtained high-precision detection of splice isoforms, including rare pre-mRNA splicing intermediates. MPE-seq uses pools of reverse-transcription primers to facilitate enrichment of splice isoforms and pre-mRNA splicing intermediates.